THE ROLE OF THE STATE IN SHARIA BANKING RESILIENCE DURING THE COVID-19 PANDEMIC: PERAN NEGARA DALAM KETAHANAN PERBANKANSYARIAH DI MASA PANDEMI COVID-19 - Juang Ananda, Muhammad (UPMI Proceeding Series, 2023)
This research aims to determine the effect of variations in agility training on soccer dribbling skills in PBD Medan Cadet High School players. The method used in this research is a quantitative experimental method. The basis for using this method is an experimental activity which begins by giving treatment to the subject which ends with a form of test to determine the effect of the treatment that has been given. The research design used in this research is in the form of One Group Pretest and Posttest Design, namely an experiment carried out in one group without a comparison group. From the two opinions above, it can be concluded that what is meant by population is the entire research subject used as research targets. The population in this study were all SMA TARUNA PBD MEDAN players, totaling 126 people. The samples taken in this research were the 2001 age group TARUNA PBD MEDAN SMA players, which actually numbered 21 people, however when the research was being carried out one of the players was sick so the sample size became 20 people. The data collection technique in this research used a dribbling skills test. Based on the paired samples statistics table above, it can be seen that the average value for pretest data is 21.27 and the average value for posttest data is 17.95. These results show that the dribbling skills of SSB Bina Taruna Tambakromo players in 2015 after practicing with agility training increased by 3.32 or 18.49% from the pretest. In this case, it can be said that the influence that various agility training exercises have on soccer dribbling skills is 18.49%.